Pengembangan Model Good Governance Pemerintahan Desa Melalui Penguatan Peran Badan Permusyawaratan Desa di Kecamatan Way Sulan Kabupaten Lampung Selatan - Rusmianto Rusmianto; Maryani Maryani (UNIVED Press, 2022)
The purpose of this study is to develop a model of village good governance through strengthening the role of the Village Consultative Body (BPD). This study uses a research and development method developed by Borg (2003) which was carried out over seven months of activities covering the stage of model development, based on data obtained through preliminary research and information gathering, designing initial models, conducting trials and validating expert teams, revising models, and producing good governance models of village governance through strengthening the role of the Village Consultative Body. The village government Good Governance model has been successfully developed through the strengthening of the Village Consultative Body (BPD) which has 4 stages, namely: the preparatory stage, the analysis phase, the implementation and implementation stage, and the reporting and output stages. The preparation phase has 3 stages starting from the selection and determination of the members of the Village Consultative Body (BPD), the orientation of the elected Village Consultative Body (BPD), and the preparation of the annual work plan of the Village Consultative Body (BPD). The analysis phase is carried out through musdes. The implementation and implementation stages have 2 stages. Starting from the discussion and ratification of village regulations, and the implementation and implementation of village regulations.